PENGARUH LEVERAGE, CAPITAL EXPENDITURE, DAN GROWTH OPPORTUNITIES TERHADAP CASH HOLDING - Vincensius Andreas; Kurniawan Tjakrawala (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the role of leverage, capital expenditure, and growth opportunities related to their effect on the value of cash holdings in property & real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2015 to 2019. The sample in this study This was taken through purposive sampling method and the valid data were 95 data from 19 companies. Data collection techniques were assisted by using Microsoft Excel 2010 program and data processing was carried out using multiple regression analysis assisted by the SPSS (Statistical Product and Service Solution) version 25 program. The results showed that leverage and capital expenditure had a negative and significant effect on cash holding, while growth opportunities have a positive and insignificant effect on cash holding. The implication of this research is the need for an active management role to be able to always create optimal cash holding value within the company to minimize existing risks and increase company value.